FINANCIAL RESILIENCE TO THE ECONOMIC SHOCK OF COVID-19: AN EMPIRICAL STUDY OF ENTERPRISES IN SERBIA - Jevtović, Danko; Stefanović, Nikola (The European Journal of Applied Economics, 2026)
This paper examines how COVID-19 affected medium and large enterprises in Serbia, revealing that size and ownership structure in this transitional economy challenge documented effects. Using panel data from Serbian enterprises (n = 3,020, period: 2018-2023), we employ fixed-effects regression with robust standard errors to analyse differential impacts. Large enterprises experienced statistically significant 19.4% higher operating revenues during COVID and 33.7% post-COVID compared to medium-sized firms (differential effects from baseline). Profitability patterns diverged as large private firms improved their operating margins by 4.1-6.8 percentage points, while state-owned firms experienced margin compression of 15.6-33.1 percentage points, despite having a six times larger asset base. Foreign ownership showed no statistically significant performance advantage. We concluded that institutional context could overturn established resilience patterns, indicating that models developed in advanced economies may not be directly transferable to transitional economies.